LEGAL CONCEPTIONS ON THE PROFESSIONAL IDENTITY CODE (CIP), GRANTED BY THE STATUS OF MATERIALIZATION OF THE SOCIAL CONTRACT BETWEEN THE CONFEF / CREF SYSTEM AND THE SOCIETY (Fiep Bulletin - online, 2017)
The purpose of this article is to offer Recipients and Beneficiaries the importance of CIP when in the exercise of the regulated profession, in kind, since it contains in its various fields the necessary information that externalize the social contract that the CONFEF / CREFs System Obliged to fulfill, guaranteeing the quality of the services offered by its registered, corroborated by the legal order of the country, which goes from the Federal Constitution of 1988 until the Technical Notes of the system.
Keywords: Social Contract; Responsibility; Intervention